Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species - Truong, Lam Xuan; Bozdoğan, Hakan; Nguyen, Lien Thi Phuong (Zootaxa, 2019)
Two species of the genus Orancistrocerus van der Vecht, 1963 from Vietnam are recorded. Of them, a new species, O. altus sp. nov. from Lang Son province in the northern part of Vietnam is described and illustrated. In addition, one subspecies, O. aterrimus nigriceps van der Vecht, 1963 is newly recorded from China.